2022
DOI: 10.3390/ma15062271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar Addition on Mechanical Properties, Thermal Stability, and Water Resistance of Hemp-Polylactic Acid (PLA) Composites

Abstract: The present study investigated the effect of biochar (BC) addition on mechanical, thermal, and water resistance properties of PLA and hemp-PLA-based composites. BC was combined with variable concentration to PLA (5 wt%, 10 wt%, and 20 wt%) and hemp (30 wt%)-PLA (5 wt% and 10 wt%); then, composites were blended and injection molded. Samples were characterized by color measurements, tensile tests, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and water contact angle analysis. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…15% for the PP/char composites. The same result of dimensional stabilization and global improvement of resistance to thermal degradation by adding BC particles to WPC was also confirmed through a study conducted by DeVallance et al [ 54 , 55 ]. A variation in final composite properties related to pyrolysis temperature was also highlighted in a polypropylene/poly (octene-ethylene) copolymer (POE) (70/30 wt.%) blend [ 56 ], in which 10 and 20 wt.% of high-temperature pyrolyzed biocarbon (HTBioC) and low temperature pyrolyzed biocarbon (LTBioC) from Miscanthus were added.…”
Section: Polymer-based Composites Containing Bcpsupporting
confidence: 61%
“…15% for the PP/char composites. The same result of dimensional stabilization and global improvement of resistance to thermal degradation by adding BC particles to WPC was also confirmed through a study conducted by DeVallance et al [ 54 , 55 ]. A variation in final composite properties related to pyrolysis temperature was also highlighted in a polypropylene/poly (octene-ethylene) copolymer (POE) (70/30 wt.%) blend [ 56 ], in which 10 and 20 wt.% of high-temperature pyrolyzed biocarbon (HTBioC) and low temperature pyrolyzed biocarbon (LTBioC) from Miscanthus were added.…”
Section: Polymer-based Composites Containing Bcpsupporting
confidence: 61%
“…It was reported that tensile strength and modulus increased with increasing BC loadings from 5% to 30%. Zouari, et al have prepared biocomposites using PLA, BC, and hemp fibers [ 19 ]. The results showed that upon adding 5 wt% BC, the tensile strength was increased, while Arrigo et al reported that tensile modulus values increase with increasing BC loading in PLA/BC composites, prepared by melt mixing or solvent evaporation [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is an abundant and renewable material, prepared from many types of biomass, including waste and low-value feedstocks. It has received increasing attention due to its high carbon content, large specific surface area, distribution of pore size [ 13 ], hydrophobicity [ 17 , 18 , 19 ], electrical conductivity [ 16 , 19 , 20 ], and stable structure [ 17 , 20 ]. These physiochemical properties may vary based on the preparation conditions, like pyrolysis temperature, heating rate, particle size, and composition of feedstock [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of F1 resulted in further structural changes in the hemp fibers observed from the loss in fiber flexibility, causing a color change that becomes more apparent after the biocomposite fabrication. Indeed, achieving a consistent color is one of the most difficult criteria for reinforced polymeric composites [ 36 ]. The density of all the biocomposites was determined based on EVS-EN ISO 1183-1, with ethanol as the displacement medium.…”
Section: Methodsmentioning
confidence: 99%